Protective effect of curcumin on lead acetate-induced testicular toxicity in Wistar rats - Sri Agus Sudjarwo; Giftania Wardani Sudjarwo; Koerniasari (Wolters Kluwer Medknow Publications, 2017)
In recent years, the use of the antioxidant in reducing heavy metal toxicities has increased worldwide. Curcumin has been reported to have a strong antioxidant activity. In this study, we investigated the protective effects of curcumin on lead acetate-induced testicular damage in rats. The sample used 40 male rats divided into 5 groups: negative control (rats were given daily with corn oil); positive control (rats were given daily with lead acetate 50 mg/kg BW orally once in a day for 35 days); and the treatment group (rats were given the curcumin 100 mg, 200 mg, and 400 mg/kg BW orally once in a day for 40 days, and on the 5th day, were given lead acetate 50 mg/kg BW one h after the curcumin administration). After 40 days, levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GPx) in testicular tissue, and sperm count, motility and viability in the epididymis were measured in rats. Testis samples were also collected for histopathological studies. Results showed that lead acetate administration significantly decreased the SOD, GPx, and increased MDA levels. Lead acetate also decreased the sperm count, motility, viability, and altered histopathological testis (testicular damage, necrosis of seminiferous tubules and loss of spermatid) compared to the negative control. However, administration of curcumin significantly improved the histopathological in testis, increased the sperm count, motility, viability, and also significantly increased the SOD, GPx, and decreased MDA in testis of lead acetate-treated rats. From the results of this study we concluded that the curcumin could be a potent natural product provide a promising protective effect against lead acetate induced testicular toxicity in rats.